Happiness and social appearance anxiety in overweight young girls - Unver, H.; Kurt, N.; Sahin, F. Bicer (Verduci Publisher, 2022)
OBJECTIVE: This research was conducted to determine the relationship be-tween social appearance anxiety and happiness in overweight young girls. SUBJECTS AND METHODS: This is a correlational descriptive study and the study sample included 343 overweight young female students from a university in eastern Turkey. A Personal Information Form, the Oxford Happiness Questionnaire-Short Form (OHQ-SF), and the Social Appearance Anxiety Scale (SAAS) were used for data collection. Descriptive statistics (percentage, mean, standard deviation), independent-samples t-test, analysis of variance, and correlation and regression analyses were used in data analysis. RESULTS: The mean age of the participants was 21.55 +/- 3.03 years. About a third of the participants (30.6%) was composed by year 3 university students, 60.6% had an income level equal to their expenditure level, and 50.7% was residing in the city center. The OHQ-SF mean total score of the participants was 17.03 +/- 5.86, and the SAAS mean total score was 43.36 +/- 17.07. There was a moderate negative correlation between the mean scores of the OHQ-SF and the SAAS (r:-.547, p < 0.001). Social appearance anxiety explained 30% of happiness in young girls participating in the study (beta:-.547, p < 0.001). CONCLUSIONS: Happiness in young girls was effective on social appearance anxiety. Health professionals may also evaluate the level of happiness in the care and counseling services they provide to young girls during extraordinary circumstances such as the COVID-19 pandemic.
Keywords: Anxiety; Happiness; Students; Social